Pengembangan E-Modul Berbasis Android Untuk Materi Sistem Komputer Pada Mata Pelajaran Informatika Kelas X SMA - Aprillia Bellanda Firmansyah; Cindy Cahyaning Astuti (Indonesian Journal Publisher, 2026)
This study aims to develop an android-based e-module for Computer Systems material in Informatics subjects for Grade X senior high school students. The research employed a Research and Development (R&D) method using the ADDIE model, limited to the analysis, design, and development stages. The e-module was developed using the Kodular platform and integrated multimedia elements such as text, images, videos, and interactive quizzes to support independent learning. Data were collected through validation sheets from media experts and material experts, as well as student response questionnaires in a limited trial. Data analysis used a Likert scale to determine product feasibility. The results showed that the media expert validation reached 87,27%, material expert validation reached 92,73%, and student responses reached 83,82%, all categorized as very feasible. Therefore, the developed e-module is suitable for use as an interactive learning medium.